Green Office Concept Assessment Study In The Council Show The Office Care - Endang Supriyadi; Maya Sofiana; Rita Wahyuni (Majalah Ilmiah Bijak, 2020)
One of the global problems that is currently happening is increasingly serious environmental damage.  Offices from companies/organizations have a major contribution to environmental damage. Various calmities that occur at this time, are not accidental, Fire, landslides, and floods are indications of environmental damage. With these conditions various efforts by the green movement were made to create environmentally friendly offices.  From the top level to the bottom, companies/organizations must caretop level to the bottom, companies / organizations must care and participate with the environment. Participating in realizing office buildings that are environmentally friendly is not necessary with activities that require large amounts of energy, time and cost, but enough for activities that we consider small but have a big impact on saving the environment are very meaningful, such as energy efficiency (saving electricity and water) and greening including.   The purpose of this paper is to describe the alternative strategic steps taken to achieve the concept of green office to create environmentally friendly offices. The writing method used is the research methodology used in this study using descriptive research methodology or literature review.  The results showed that there were company committed to implementing a green office including PT Mandiri (Persero) Tbk., Surakarta in Central Java